Pengaruh Citra Destinasi dan Electronic Word Of Mouth (E-WOM) Dalam Menentukan Kunjungan Wisata (Studi Kasus Pada Kampoeng Kopi Banaran Semarang) - Shalsha Afifah Ayumi; Erlyna Wida Riptanti; Isti Khomah (Politeknik Piksi Ganesha Indonesia, 2022)
Agrotourism is currently very popular with tourists because it can increase knowledge and experience. Tourists currently choose destinations based on information from reviews on social media, another name is electronic word of mouth. The COVID-19 pandemic has led to a decline in visitor, strategies are needed to maintain and improve the quality of tourism. Purpose of this research to find the influence of destination image and E-WOM on tourist visits. The basic method is descriptive analytic with research techniques. 150 respondents were used for the sample. The analytical tool in this research is SEM-PLS. The results showed that the destination image had no effect on determining tourist visits, but after being mediated by visitor interest, the destination image had an influence on determining visits. The E-WOM variable directly or mediated by visitor interest have an impact on determining tourist visits.